Identification of vitamin B1 metabolism as a tumor-specific radiosensitizing pathway using a high-throughput colony formation screen - Tiwana, Gaganpreet S; Prevo, Remko; Buffa, Francesca M; Yu, Sheng; Ebner, Daniel V; Howarth, Alison; Folkes, Lisa K; Budwal, Balam; Chu, Kwun-Ye; Durrant, Lisa; Muschel, Ruth J; McKenna, W Gillies; et al. (Oncotarget, 2015)
Colony formation is the gold standard assay for determining reproductive cell death after radiation treatment, since effects on proliferation often do not reflect survival. We have developed a high-throughput radiosensitivity screening method based on clonogenicity and screened a siRNA library against kinases. Thiamine pyrophosphokinase-1 (TPK1), a key component of Vitamin B1/thiamine metabolism, was identified as a target for radiosensitization. TPK1 knockdown caused significant radiosensitization in cancer but not normal tissue cell lines. Other means of blocking this pathway, knockdown of thiamine transporter-1 (THTR1) or treatment with the thiamine analogue pyrithiamine hydrobromide (PyrH) caused significant tumor specific radiosensitization. There was persistent DNA damage in cells irradiated after TPK1 and THTR1 knockdown or PyrH treatment. Thus this screen allowed the identification of thiamine metabolism as a novel radiosensitization target that affects DNA repair. Short-term modulation of thiamine metabolism could be a clinically exploitable strategy to achieve tumor specific radiosensitization.